Type and Intensity as Key Variable of Exercise in Metainflammation Diseases: A Review - Figueiredo, Caique [UNESP]; Padilha, Camila S. [UNESP]; Dorneles, Gilson P.; Peres, Alessandra; Krüger, Karsten; Rosa-Neto, José Cesar; Lira, Fabio S. [UNESP] (Thieme, 2022)
Monocyte and lymphocyte subpopulations exhibit functions that vary between the anti- and pro-inflammatory spectrum, such as classic CD16- and non-classical CD16+monocytes, as well as T helper 2 lymphocytes (Th2), the Th1/Th17 lymphocytes ratio, and T regulatory lymphocytes (Treg). Metabolic disease-associated inflammation is accompanied by an imbalance in monocyte and lymphocyte phenotypes and functionality, as well as a stronger proportion of inflammatory subpopulations. These changes appear to be important for the development and progression of diseases like diabetes and cardiovascular disease. On the other hand, the regular practice of physical exercise is an important tool to restore the functionality of monocytes and lymphocytes, and to balance the subtypes ratio. However, key variables regarding exercise prescription, such as the type of exercise, intensity, and volume differentially impact on the acute and chronic immune response in individuals diagnosed with meta-inflammation diseases. Here, we discuss the impact of different physical exercise protocols, acutely and chronically, on monocytes and lymphocytes of individuals with metabolic disease-associated inflammation. In this review, we focus on the best effects of different exercise protocols to dose the exercise pill in different inflammatory status.
Keywords: exercise program; lymphocytes; metabolic diseases; monocytes